Metabolic Recycling Enhances Proliferation in MYC‐Transformed Lymphoma B Cells. Issue 2 (23rd November 2022) - Zhang, Cissy; Hoang, Giang; Attarwala, Nabeel; Cooper, Arthur J. L.; Asaka, Ryoichi; Le, Anne
Abstract: Relapses negatively impact cancer patient survival due to the tumorigenesis ability of surviving cancer cells post‐therapy. Efforts are needed to better understand and combat this problem. This study hypothesized that dead cell debris post‐radiation therapy creates an advantageous microenvironment rich in metabolic materials promoting the growth of remaining live cancer cells. In this study, live cancer cells are co‐cultured with dead cancer cells eradicated by UV radiation to mimic a post‐therapy environment. Isotopic labeling metabolomics is used to investigate the metabolic behavior of cancer cells grown in a post‐radiation‐therapy environment. It is found that post‐UV‐eradicated dead cancer cells serve as nutritional sources of "off‐the‐shelf" and precursor metabolites for surviving cancer cells. The surviving cancer cells then take up these metabolites, integrate and upregulate multiple vital metabolic processes, thereby significantly increasing growth in vitro and probably in vivo beyond their intrinsic fast‐growing characteristics. Importantly, this active metabolite uptake behavior is only observed in oncogenic but not in non‐oncogenic cells, presenting opportunities for therapeutic approaches to interrupt the active uptake process of oncogenic cells without affecting normal cells. The process by which living cancer cells re‐use vital metabolites released by dead cancer cells post‐therapy is coined in this study as "metabolic recycling" of oncogenic cells. Abstract : This study finds that a post‐UV‐therapy environment containing dead cancer cells promotes the proliferation of live cancer cells by serving as a source of "off‐the‐shelf" and precursor metabolites, which the live cancer cells can absorb and incorporate into their metabolism. This phenomenon is only observed in oncogenic cells, but not in non‐oncogenic cells, providing a potential target for cancer therapy.